PENGARUH STATUS GIZI IBU SELAMA KEHAMILAN DAN MENYUSUI TERHADAP KEBERHASILAN PEMBERIAN AIR SUSU IBU - Anies Irawati; Agus Triwinarto; Salimar Salimar; Irlina Raswanti (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2003)
EFFECT OF MATERNAL NUTRITION STATUS DURING PREGNANCY AND LACTATION TO SUCCESSFULLY BREASTFEEDING.Background: Infant should be only got breast milk in first six-months, but most of mothers do not successfully breastfed their infant because infant consumed low energy from breast milk. Maternal nutrition status during pregnancy and lactation may contribute to successful breastfeeding. During lactation, there is mobilization of fat to produce breast milk.Objective: The objective of this study is to evaluate contribution of maternal nutrition status before pregnancy, during pregnancy and lactation to successful breastfeedingMethods: In the first four-month of life, if infant consumed energy from breast milk ≤ 65% of RDA categorized as not successful breastfeeding, and if infant consumed energy from breast milk > 65% of RDA categorized as successful breastfeeding.Results: The result shows that maternal nutrition status during pregnancies doesn't contribute to successful breastfeeding. Maternal nutrition status during lactation significantly contributes to successful breastfeeding after controlling other factors (mother factors, infant factors, food pattern and social economics factors). During lactation, the risk of thin mothers (IMT < 18.5) to unsuccessful breastfeeding is 2.26 to 2.56 times compared to normal mothers (IMT ≥ 18.5-25.0) (RR = 2.26 to RR = 2.56).Conclusion: Mother should consume more energy and protein to achieve successful breastfeedingKeywords: successfully breastfeeding